The relation between child death and child maltreatment. Issue 3 (21st February 2006) - Jenny, C; Isaac, R
Abstract : The death of a child is a sentinel event in a community, and a defining marker of a society's policies of safety and health. Child death as a result of abuse and neglect is a tragic outcome that occurs in all nations of the world. The true incidence of fatal child abuse and neglect is unknown. The most accurate incidence data of such deaths have been obtained from countries where multi-agency death review teams analyse the causes of child fatalities, as is done in the United States and Australia.